Prevalence of poor glycemic and blood pressure control and pattern of drug use among primary health-care outpatients in Al Ahsa Saudi Arabia - Emeka, Promise M; Al Mukalaf, Ahmed; Al Helal, Hussien; Khan, Tahir M.; Almukalf, Mishial A. (International Journal of Health Sciences, 2017)
Objectives: To assess drug use pattern and the effect on glycemic and blood pressure (BP) control in type 2 diabetes mellitus (T2DM) and hypertensive patients. Furthermore, to evaluate the duration of drug use and antecedence in diagnosis. Methodology: A cross-sectional study design, comprising interview/questionnaire targeting outpatients attending primary health centers in Al Ahsa was adopted. During the interview, their fasting blood glucose, weight, and height were measured, along with their BP. Time and duration of drug use were recorded. The history, sociodemographic data and the presence of any other disease conditions were also documented. Results: The highest number of uncontrolled BP and poor glycemic control was among the age group of 45 and 49 years. Significant number of the patients (92.9%) had body mass index >30 kg/m2. The prevalence of developing hypertension before T2DM among participants was 59.9%. A significant number (84%) had uncontrolled hypertension, and 67.3% had uncontrolled T2DM. Drug use pattern revealed single or combinations according to clinical guidelines initially but did not follow through in meeting targets. Majority received angiotensin converting enzyme inhibitors, amlodipine or atenolol for BP control and metformin for T2DM. Patients diagnosed between 1 and 5 years displayed significant poor glycemic and BP control. Significantly, most patients appeared to have been on same prescriptions for a longer time without review. Conclusion: Poor glycemic and BP controls observed in this study could be due to deficient treatment strategy among others. Patients were, however, not adequately managed in line with prescribed clinical guidelines.